Implementation of public tasks in the light of responsibility for the effective spending of public funds - Zbigniew Tetłak (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The implementation of public tasks for which public funds are spent should be recognized by striving to achieve the set goals and due diligence in managing funds. In the Public Finance Act (Article 44), the legislator linked the effectiveness of spending public funds with the effectiveness and optimization of the selection of methods for achieving set goals and the timely implementation of incurred obligations. Public tasks defined in European Union law and transferred to Polish legislation most often have precisely defined objectives, for example in the form of unambiguous indicators. The problem is that the indicators are increasing year by year and the threat of high penalties for failing to achieve them. Therefore, the responsibility for the effective spending of public funds for the implementation of the indicated tasks becomes fundamental. An illustration of the above-mentioned problem are tasks in the field of municipal waste management, the goals for which are specified in the Act on maintaining cleanliness and order in municipalities, and municipal the source of their financing are funds from the garbage fee, the amount of which is determined by the council.